Inovasi Teknologi Budidaya Sayuran pada Lahan Kering Melalui Pupuk Organik dan Vertikultur dengan Sistem Fertigasi Sumbu di Desa Napan Kabupaten Timor Tengah Utara NTT - Sipayung, Boanerges Putra; Tobing, Wilda Lumban; Tefa, Azor Yulianus; Epriliati, Indah; Widyawati, Paini Sri; Laurentinus, Hadi Santoso; Buan, Febrya Christin Handayani; Silla, Misail Epainetus (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the innovation of farmer groups in implementing vegetable cultivation technology in dry land through organic fertilizer and verticulture with a wick fertigation system. The method applied in this service uses counseling and training (learning by doing). The implementation was carried out on the agricultural land of the Nunuh Naek and Taruna Tani Farmer Group in October – December 2023. This activity involved the Napan Village Government and the North Bikomi District Agricultural Extension Officer to support the partner team together with the Implementing Team (University of Timor) and the Accompanying Team (Widya Catholic University Mandala Surabaya) to develop regional development programs in accordance with the relationship between Kosabangsa and RPJMD activities. The results of the service concluded that there was an increase in the ability of farmer groups to independently design verticulture with a wick fertigation system as an innovation in cultivating vegetables on dry land; able to apply Ribon Atom I as a soil amendment as well as adding nutrients to plants; and increasing the ability of partners in agribusiness management of horticultural farming.